PERCEPTION OF ONLINE VERSUS PHYSICAL LEARNING AMONGUNIVERSITY STUDENTS - Ramna Shafique; Muhammad Abdullah; Tooba Nasir; Sundas Salim; Sabrina Jam; Bina Fawad (Baqai Journal of Health Sciences)
Objectives: To assess the perception of online versus face-to-face learning among medical and non-medical university students of Karachi, Pakistan.